ChemInform Abstract: Mild Radical Oxidative sp3‐Carbon—Hydrogen Functionalization: Innovative Construction of Isoxazoline and Dibenz[b, f]oxepine/azepine Derivatives. Issue 17 (April 2016) - Gini, Andrea; Garcia Mancheno, Olga
Abstract: Review: [46 refs.